Energy Security in Mongolia: Current Trajectory and Future Prospects - Chatterjee, Souvik; Baitha, Subhash Kumar (Universitas Negeri Surabaya, 2021)
Mongolia is a landlocked country situated between two powerful neighbors Russia to the north, China to the south. Due to Mongolia’s geographical positioning, the country has limited diplomatic options to showcase its power both at the global and regional levels. Thus, Mongolia was forced to initiate political and economic reforms to cope up with the post-cold war global politics. In recent times, Mongolia's unexplored and abundant natural resources are key factors of Mongolia’s socio-economic development. Yet, Mongolia is often cited as an example of a “resource curse”. Mongolia was unable to use its natural resources efficiently hence suffered from resource deficient economic, political, and social challenges. Mongolia’s geographical location and its landlocked position between China and Russia constrained Mongolia’s ambition to shift from an import-based economy to an export-oriented powerful economy in North-East Asia. However, Mongolia’s natural resources, political stability, and non-alignment approach have great potential to decrease Mongolia’s overdependence on imports from neighboring countries. Mongolia in the post-cold war era regime is adopting a diverse and multilateral approach. With a brief overview of the economic, political, physical challenges faced by Mongolia, the paper highlights the potential of Mongolia’s energy sources.